PREECLAMPSIA PREDICTION AND FETAL ASSESSMENT DURING PREGNANCY - Farfán, José (2015)
Lack of risk prediction or subclinical disease identification make preeclampsia prophylaxis difficult. Some associated risk factors are chronic hypertension, gestational diabetes, multiple pregnancy and history of preeclampsia. Characteristic clinical presentation (hypertension, proteinuria and edema) has directed to potential markers that study renal function, coagulation, fibrinolytic system and platelets activity, vascular markers (fibronectin, prostacycline and thromboxane), antioxidants, placental hormones, vascular resistance, insulin resistance and glucose intolerance, among others.